Efficacy and safety of intracorneal allogenic ring segment implantation in keratoconus: 1-year results - Aşık Nacaroğlu, Şenay; Yeşilkaya, Elif Ceren; Keskin Perk, Fatma Feyza Nur; Tanrıverdi, Cafer; Taneri, Suphi; Kılıç, Aylin (Springer Nature, 2023)
BackgroundTo evaluate the safety and efficacy of corneal allogenic intrastromal ring segments in the management of keratoconus patients.MethodsThe retrospective, nonrandomized, interventional case series consisted of 65 keratoconic eyes of 49 consecutive patients who had ring segment-shaped corneal allografts (KeraNatural (R)) implanted in intrastromal tunnels created using a femtosecond laser. The main outcome measures were uncorrected visual acuity (UCVA), corrected distant visual acuity (CDVA), refraction, keratometry, and pachymetry. Computed tomography scans of the corneal surfaces were also performed preoperatively as well as 3, 6 and 12 months postoperatively.ResultsMean age was 29.5 +/- 7.3 years (median 29, range: 20-52 years). The mean UCVA improved from 0.91 +/- 0.50 logMAR preoperatively to 0.40 +/- 0.24 logMAR postoperatively at 6 month follow-up (p < 0.01) and the mean CDVA improved from 0.87 +/- 0.20 logMAR preoperatively to 0.27 +/- 0.06 logMAR postoperatively (p < 0.01). The mean spherical equivalent improved from -8.82 +/- 4.57 to -3.45 +/- 4.81D (p < 0.01). Average Keratometry decreased from 49.23 +/- 5.22 preoperatively to 45.63 +/- 4.89 D postoperatively (p < 0.01). Mean anterior and posterior maximum elevation were also decreased significantly (p < 0.01). In one patient, dislocation of the graft towards the tunnel incision site and dehiscense at the tunnel entrance were observed in the first week of the operation. Yellow-white deposits were observed in the segment tunnels in five cases after 6 months.ConclusionThis study demonstrated that implantation of corneal allograft ring segments is a viable alternative treatment for keratoconus with safety and good visual results.
Keywords: Intracorneal Allogenic; Segment Implantation